Estimate of genetic variances in eight creole maize varieties for the mexican low-land region - Muñoz Romero, Luis Ángel (2017)
The aim of this work was to estimate the combinatory aptitude, genetic variance and heterosis of eight creole corn varieties. The research work was carried in Irapuato, Guanajuato, México, during 2008 and 2009. A randomized complete block design with three replications was used to evaluate the twenty-eight crosses under method 4 Griffing (1956). Each experimental plot included four rows five meters long with a separation of 0,75 m. The general combing ability and specific (ACG and ACE) were highly significant (P<0.01) for all traits except flowering days. The dominance variance (σ2D) was larger and more important than additive variance (σ2A) for most of the traits, indicating that non- additive genetic genes were important on the expression of those traits on crosses. It was observed that varieties P6 (creole #5), P7 (creole #2) and P8 (creole San Antonio) had larger variance effects (σ2ACE) for long cob, number of rows per cob, total cob number, and grain yield. Some outstanding crosses were identified for their high grain yield as well as heterosis, mainly those that included germoplasm of creole #5, #2 and San Antonio. According to the aforementioned we recommend to draw lines from the above populations and cross them to produce hybrids.